2007
DOI: 10.1073/pnas.0607052104
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of force generation by actin filament polymerization using an optical trap

Abstract: Actin filament polymerization generates force for protrusion of the leading edge in motile cells. In protrusive structures, multiple actin filaments are arranged in cross-linked webs (as in lamellipodia or pseudopodia) or parallel bundles (as in filopodia). We have used an optical trap to directly measure the forces generated by elongation of a few parallel-growing actin filaments brought into apposition with a rigid barrier, mimicking the geometry of filopodial protrusion. We find that the growth of approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
365
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 347 publications
(388 citation statements)
references
References 44 publications
21
365
2
Order By: Relevance
“…We make the further assumption (described previously) that actin filament protrusion is mechanically stalled by the membrane tension T at the sides of the front of the lamellipodium (l~+x=2). The force acting on each filament at the sides must therefore be approximately equal to the force required to stall a single actin filament 28 , f stall , which has been measured 29,30 , so…”
Section: Nature | Vol 453 | 22 May 2008mentioning
confidence: 99%
“…We make the further assumption (described previously) that actin filament protrusion is mechanically stalled by the membrane tension T at the sides of the front of the lamellipodium (l~+x=2). The force acting on each filament at the sides must therefore be approximately equal to the force required to stall a single actin filament 28 , f stall , which has been measured 29,30 , so…”
Section: Nature | Vol 453 | 22 May 2008mentioning
confidence: 99%
“…To the best of our knowledge, only one set of experiments has reported stall force for a single growing actin filament -a value of ≈ 1pN [41]. In another set of experiments on a few actin filaments growing in parallel, Footer et al [49] reported a collective stall force of ≈ 1 pN, which is very similar to the load required to stall a single filament. In this experiment, the interpretation of filament cooperativity while pushing together against the barrier is, however, complicated by the fact that individual actin filaments may buckle before reaching their stall force, and hence, collectively the bundle may be unable to reach its full potential for force generation.…”
Section: Introductionmentioning
confidence: 62%
“…A number of experiments on force generation by an assembly of biofilaments have been reported in the literature [36,39,[41][42][43][44][45][46][47][48][49]. In view of the overall content and objective of our paper we will focus only on the experiments related to single and parallel bundles of growing biofilaments.…”
Section: Introductionmentioning
confidence: 99%
“…The bending shape of single F-actin filaments observed by fluorescence spectroscopy, was precisely exploited to measure for the first time the typical polymerization force generated by single living actin filaments [15,16]. In the optical trap experiment of Footer et al [5], a bundle of about ten filaments, with their seeds glued to a trapped colloidal particle, push with their active side (barbed end) on a fixed rigid wall. The polymerization force they progressively develop to reach equilibrium is inferred by measuring the colloidal displacement in the trap.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments on biofilaments, like actin and tubulin, to measure in supercritical conditions either the forcevelocity relationship in detectable non-zero velocity conditions [3,4], or the approach to stalling where the applied load effectively stops the net polymerization of living filaments and the stalling force is effectively measured [5], have been deviced. To simplify the analysis and to concentrate on the fundamental process of force generation by polymerizing filaments, the experiments deal with bundles of parallel filaments hitting an orthogonal moving wall, a network having strong analogy with the structure of actin filopedia [1].…”
Section: Introductionmentioning
confidence: 99%